Aplication of nanogold and nanosilver to reduce rheumatic arthritis: Case study at leprosy patients. Issue 1 (April 2021) - Taufikurohmah, T; Rusmini, R; Soepardjo, D
Abstract: This study aims to ensure the treatment of rheumatoid arthritis cases suffered by leprosy patients. Special inspection is carried out every 2 weeks during the treatment. Treatment by giving nanogold and nanosilver volunteers every morning and night as much as 20 ml 20 ppm in drinking water. The number of volunteers 24 people with an age range of 40-70 years. The sex of male volunteers is 12 people and women are 12 people. The condition is divided into 4 categories; weight, moderate, mild and cured. In the beginning, volunteers were chosen in the weight and moderate categories. Research data were medical records and interviews. The results show a gradual recovery process towards recovery. One person with an initial condition in the weight category had not recovered for 3 months of treatment. Overall there was an improvement in conditions from weight to moderate, mild and recovered. Gender has no effect on the recovery process. The conclusions of the nanogold and nanosilver case studies succeeded in alleviating to cure rheumatoid arthritis volunteers for leprosy patients. This case study has the impact give new hopes for leprosy patients to keep their spirits alive. This is very important for the future of leprosy patients free from rheumatoid arthritis.